2014
DOI: 10.1371/journal.pone.0089922
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Independent Screening Revealed Hot Spots of IncP-1, IncP-7 and IncP-9 Plasmid Occurrence in Different Environmental Habitats

Abstract: IncP-1, IncP-7 and IncP-9 plasmids often carry genes encoding enzymes involved in the degradation of man-made and natural contaminants, thus contributing to bacterial survival in polluted environments. However, the lack of suitable molecular tools often limits the detection of these plasmids in the environment. In this study, PCR followed by Southern blot hybridization detected the presence of plasmid-specific sequences in total community (TC-) DNA or fosmid DNA from samples originating from different environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
4
31
0
1
Order By: Relevance
“…Several other studies have pointed to the role of IncP-1 plasmids in the adaptation of the bacterial community to xenobiotic compounds such as pesticides released into the environment (6,12; reviewed in references 41, 42, and 43). The high abundance of the subgroups IncP-1␤, -␥, -␦, and -ε revealed in the present study confirmed previously reported findings (15,37). Although Southern blot hybridization does not provide quantitative information on specific gene copy numbers per gram of material as does quantitative PCR (qPCR), changes in the abundances of the different subgroups could be indicated which were confirmed by amplicon pyrosequencing of the trfA amplicon obtained with the same primer sets as those used for the PCR screening.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Several other studies have pointed to the role of IncP-1 plasmids in the adaptation of the bacterial community to xenobiotic compounds such as pesticides released into the environment (6,12; reviewed in references 41, 42, and 43). The high abundance of the subgroups IncP-1␤, -␥, -␦, and -ε revealed in the present study confirmed previously reported findings (15,37). Although Southern blot hybridization does not provide quantitative information on specific gene copy numbers per gram of material as does quantitative PCR (qPCR), changes in the abundances of the different subgroups could be indicated which were confirmed by amplicon pyrosequencing of the trfA amplicon obtained with the same primer sets as those used for the PCR screening.…”
Section: Discussionsupporting
confidence: 93%
“…The very high relative abundances of the promiscuous IncP-1 plasmids detected in the BPS are comparable to those seen with other "hot spots" of horizontal gene transfer such as manure, sewage, or polluted river sediments (39,40). Our data confirm the results of two recent studies using TC-DNA from different BPS which also found an unusually high abundance of IncP-1 plasmids in the BPS (15,37). Interestingly, the abundance of IncP-1 plasmids seemed to be increased in BPS bacteria, likely in response to the exposure to different types and concentrations of pesticides as recently reported by Jechalke et al (14).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations